Relationship between kind of delivery and dysmenorrhea - Nahidi, F; Bagheri, L; Jannesari, Sh (Advances in Nursing & Midwifery, 2008)
Background The term dysmenorrhea is currently used to refer to painful menstruation. The cause of primary dysmenorrhea has not been clearly elucidated. It has been said anecdotally that childbirth can ameliorate menstrual pain and some articles have proved a significant effect of childbirth on dysmenorrhea. Further investigations regarding the effects of delivery mode on dysmenorrhea has been rarely published. Purpose This analytical retrospective study was conducted to identify relationship between the modes of delivery and dysmenorrhea and to compare its severity at early and late age of childbearing in women referring to selected hospitals affiliated to Tehran Medical University in 2006. Methods 160 women between 36 and 44 were selected by convenience sampling method. An information form was used for data collection, validated and made reliable by content and test-retest methods respectively. Results Findings showed a significant decrease in dysmenorrheal pain at the time of study compared with early age of childbearing, before the first delivery. In women with dysmenorrhea, Caesarian rate was more than normal vaginal delivery and 46.2% of them had chosen Caesarian for their delivery. Conclusion According to the results, delivery decreases dysmenorrheal pain. In addition, dysmenorrhea had been experienced more in women who were delivered by Caesarian. Therefore, the importance of normal vaginal delivery should be more emphasized in this regard. Keywords Dysmenorrhea, Delivery، Caesarian.